2016
DOI: 10.12982/cmujns.2016.0016
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Glycyrrhizic Acid and Microbial Decontamination of Glycyrrhiza glabra (licorice) by Gamma Radition

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Lee et al (2005) also revealed that gamma irradiation up to 25 kGy did not have any effect on the antioxidant activity of green tea byproducts and green tea leaf extract. Meanwhile, Pewlong et al (2016) reported an increase of glycyrrhizic acid in licorice powder for gamma irradiation at a dose 15 kGy.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (2005) also revealed that gamma irradiation up to 25 kGy did not have any effect on the antioxidant activity of green tea byproducts and green tea leaf extract. Meanwhile, Pewlong et al (2016) reported an increase of glycyrrhizic acid in licorice powder for gamma irradiation at a dose 15 kGy.…”
Section: Discussionmentioning
confidence: 99%